INOVASI KURIKULUM PENDIDIKAN AGAMA ISLAM - Mohammad Al Farabi; Budiman Budiman; Muhammad Nazri; Muhammad Amran; Faisal Faisal (Jurnal Ilmiah Hospitality, 2022)
Among the goals of Islamic education is to increase human intelligence and spirituality for individuals. Quality of life for individuals is part of the problems that are approached in the world of education regarding the curriculum which is the center of the educational forum. The curriculum that formulates the path of educational practice and is like a stakeholder in the education system, so that when the study program does not have innovation that is comparable to the direction of world change, the learning process obtained cannot increase the strength of students to compete in the industrial world.